LOCALITY IN CONSTRUCTING CULTURAL IDENTITY (A REVIEW ON SEMARANG BATIK ART) - Syakir, Syakir; Soesanto, Soesanto; Tohir, Mujahirin (The Journal of Educational Development, 2017)
In the context of identity, batik is a form of expression of art with unique features that become the identity or may potentially become a cultural identity for either local or national identity. As the capital of Central Java, Semarang has built an identity through batik that depicts Semarang as having a batik culture. The construction of identity in Semarang batik began from searching for local identities by related actors, either personal or communities or organizations, who collectively explore ideas from locality. Locality includes natural, physical, and social-cultural environments. Through creativity in batik art, those ideas are conveyed in innovation and production of distinctive batik that is Semarang-style batik. This distinction represents Semarang locality that forms Semarang identity. The identity that is created as a product of that culture is continuously developed and preserved through enculturation by education in families, schools, and the society.